Joint waveform and precoding design for coexistence of MIMO radar and MU‐MISO communication. Issue 7 (25th March 2022) - Wei, Tong; Wu, Linlong; Shankar Mysore Rama Rao, Bhavani
Abstract: The joint design problem for the coexistence of multiple‐input multiple‐output (MIMO) radar and multi‐user multiple‐input‐single‐output (MU‐MISO) communication is investigated. Different from the conventional design schemes, which require defining the primary function, we consider designing the transmit waveform, precoding matrix and receive filter to maximize the radar SINR and the minimal SINR of communication users, simultaneously. By doing so, the promising overall performance for both sensing and communication is achieved without requiring parameter tuning for the threshold of communication or radar. However, the resulting optimization problem which contains the maximin objective function and the unit sphere constraint, is highly nonconvex and hence difficult to attain the optimal solution directly. Towards this end, the epigraph‐form reformulation is first adopted, and then an alternating maximisation (AM) method is devised, in which the Dinkelbach's algorithm is used to tackle the nonconvex fractional‐programing subproblem. Simulation results indicate that the proposed method can achieve improved performance compared with the benchmarks.